Batik Parang Winongo sebagai Media Pembelajaran Nilai-nilai Pancasila dalam Menghadapi Tantangan Globalisasi - Junita, Fitri; Widodo, Wahono; Istig’faroh, Nurul (Tumoutou Social Science Journal, 2024)
The current globalization has brought about rapid socio-cultural changes. The values of Pancasila as the foundation of the Republic of Indonesia have an important role in shaping the identity and character of the nation. The purpose of this study is to increase social awareness and interest of the younger generation in the nation's cultural heritage, while equipping them with strong moral provisions to face the challenges of the era of globalization. The type of method used in writing this research is a qualitative descriptive approach. The main purpose of qualitative descriptive research is to describe or explain the phenomenon or context of the research to understand the reasons, motivations, meanings, or concepts related to the research subject. The results of qualitative descriptive research are interpreted by considering the context, relevant theories, and findings that emerge during the analysis. Data collection was carried out using triangulation, which combines several techniques. The use of triangulation techniques aims to match data obtained from one source with data obtained from other sources. The techniques used are participant observation, in-depth interviews, and document studies. The results of this study are Parang Winongo batik as a learning medium in Pancasila Education subjects that can increase social awareness and interest of the younger generation in the nation's cultural heritage, while equipping them with strong moral provisions to face the challenges of the era of globalization. The impact of Parang Winongo batik as a learning medium in schools is not only a cultural heritage, but also a valuable asset in efforts to build national character, and can be a powerful tool to form a young generation with character, culture, and love for the country.